2013
DOI: 10.1136/bmj.f1865
|View full text |Cite
|
Sign up to set email alerts
|

Persistent pain and sensory disturbances after treatment for breast cancer: six year nationwide follow-up study

Abstract: Objective To examine the development of persistent pain after treatment for breast cancer and to examine risk factors associated with continuing pain.Design Repeated cross sectional study in a previously examined nationwide cohort. All eligible women who underwent surgery for primary breast cancer in Denmark in 2005 and 2006 and were examined in 2008 were surveyed again with the same questionnaire. Setting Surgical centres in Denmark.Main outcome measures Prevalence, location, and severity of persistent pain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
176
4
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(200 citation statements)
references
References 37 publications
(35 reference statements)
11
176
4
9
Order By: Relevance
“…The presence of pain in this study had higher frequency than in the studies found in the literature, for which rates ranged from 22% to 55% [20][21][22][23] . The findings of this research reveal the high prevalence of chronic pain, but there was no statistically significant difference between the groups.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The presence of pain in this study had higher frequency than in the studies found in the literature, for which rates ranged from 22% to 55% [20][21][22][23] . The findings of this research reveal the high prevalence of chronic pain, but there was no statistically significant difference between the groups.…”
Section: Discussioncontrasting
confidence: 53%
“…As for the intensity of the pain, in the comparison between groups, there was no difference for any of the locations assessed, with the average pain intensity being low, except for the arm. For this last one, the average pain intensity was considered moderate 22 in both groups. This fact does not allow us to indicate a cause and effect relationship, because this is a cross-sectional study 24 and variables related to the surgery, such as nerve damage, were not controlled 25 .…”
Section: Discussionmentioning
confidence: 99%
“…As chronic pain may be severe in 2-10% of these patients, chronic postoperative pain represents a major, mostly undiagnosed clinical issue (1,2) . Many studies reported that development of chronic pain after breast surgery is the most common problem with an incidence of 25-60% depending on the definition of incidence, measurement and treatment methods (3) . After ruling out other causes of pain such as recurrent painful episodes, chronic postoperative pain is defined as having pain related to surgical site over 3 months following surgery (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that development of chronic pain after breast surgery is the most common problem with an incidence of 25-60% depending on the definition of incidence, measurement and treatment methods (3) . After ruling out other causes of pain such as recurrent painful episodes, chronic postoperative pain is defined as having pain related to surgical site over 3 months following surgery (3) . Chronic postoperative pain has a negative effect on the quality of life and creates important economic consequences for health system.…”
Section: Introductionmentioning
confidence: 99%
“…O quadro álgico pode ocorrer em qualquer fase da doença, na maioria das vezes, decorrente de complicações do pós--operatório, radioterapia ou quimioterapia 20 . Em nosso estudo, não foi observada correlação entre o domínio dor e aspectos emocionais, acreditando-se na influência negativa dos aspectos emocionais na intensidade da dor crônica.…”
unclassified